Regulation of F-box proteins by noncoding RNAs in human cancers. (1st December 2019) - Lin, Min; Xu, Yichi; Gao, Ying; Pan, Chunyu; Zhu, Xueqiong; Wang, Zhi-wei
Abstract: F-box proteins (FBPs) are proteins containing an F-box domain and are one of three subunits in SKP1–Cullin1–F-box protein (SCF) E3 ligase complexes. Accumulated evidence has shown that FBP regulates tumorigenesis and the progression of human cancer via ubiquitination and degradation of downstream substrates, which can be oncoproteins or tumor suppressors. Emerging evidence has revealed that noncoding RNAs (ncRNAs) govern the expression of FBP in human cancers. Specifically, microRNAs (miRNAs), long ncRNAs (lncRNAs), and circular RNAs (circRNAs) have been shown to govern FBP expression in malignancies. Therefore, in this review article, we discuss how miRNAs target FBPs and participate in tumorigenesis and tumor progression. Moreover, we briefly highlight the role of lncRNAs and circRNAs in the regulation of FBPs in cancer. Therefore, targeting ncRNAs could be a novel approach to regulate FBPs for anticancer therapy. Highlights: F-box proteins are critical involved in tumorigenesis and progresses. F-box proteins have diverse functions in various cancers. F-box proteins are regulated by ncRNAs. Targeting F-box proteins via ncRNAs is promising strategy for cancer treatment.